Non‐monophyly of Buglossoides (Boraginaceae: Lithospermeae): Phylogenetic and morphological evidence for the expansion of Glandora and reappraisal of Aegonychon. Issue 5 (1st October 2014) - Cecchi, Lorenzo; Coppi, Andrea; Hilger, Hartmut H.; Selvi, Federico
Abstract: The phylogeny of the small Old World genus Buglossoides and its position in tribe Lithospermeae was investigated using nrDNA and cpDNA sequences and morphology. Maximum parsimony and Bayesian analyses of ITS‐5.8S and trnL‐trnF IGS datasets consistently show that this group is close to Glandora and Lithospermum but not monophyletic. Of the seven species usually included, two were retrieved in the genus Glandora, i.e., B. goulandrisiorum from northern Greece and B. gastonii from the western Pyrenees. Based also on morphology and ecology, the placement of these two rare, rupicolous endemics in Glandora is here advocated and new combinations are made. The rest of Buglossoides includes two early‐diverging clades, one with annual taxa of section Buglossoides and one with the three perennials of section Margarospermum . Morphological, palynological and ecological data support the separation of these two groups in distinct genera, Buglossoides s.str. and the old but largely neglected Aegonychon. Within Buglossoides, two main clades correspond to the B. arvensis and B. incrassata complexes. These show a largely sympatric distribution from the south Mediterranean to central and northern Europe. Combined with their strong phenotypic polymorphism, this causes difficulties in the distinction between taxa of the two clades, especially without characteristic cotyledons or fruiting material. Molecular and morphological evidence clearly support the transfer of the west Mediterranean B. arvensis subsp. permixta to the B. incrassata complex.